Evaluating ChatGPT in relation to its effectiveness for argumentative essay writing - Ljubojevic, Danijela (Vestnik za tuje jezike, 2025)
The rapid advances in artificial intelligence, particularly in language models like ChatGPT, have led educators to re-evaluate traditional teaching methods, especially regarding essay writing assignments. Teachers express growing concern that AI-generated essays could compromise the essence of student writing, potentially diminishing critical skills such as deeper analysis and personal expression. This case study explores an innovative approach to integrating ChatGPT within the classroom by making use of the flipped learning model and sentence skeletons technique. For the purpose of this research four argumentative es-says were generated by ChatGPT. These essays were assessed by four independent teachers using a structured checklist. The checklist focused on essay structure, cohesion and coher-ence, argument presentation, vocabulary use, and grammatical accuracy, and the intellectual standards necessary for critical thinking, such as clarity, precision, accuracy, depth, breadth, logic, significance, relevance, and fairness. The results revealed that ChatGPT excels in essay writing in terms of essay structure, developing an appropriate introduction, body, and conclusion. It generates high-quality argumentative essays, rich in vocabulary (C1–C2 CEFR level), and text linking (numerous transitions signals and linkers). On the other hand, these essays did not follow word limit requirements, write a funnel introduction/paragraph, provide opposing arguments, and give personal opinions. When it comes to the element of critical thinking, the generated essays lacked depth, breadth, and fairness. Nevertheless, the findings indicate that ChatGPT holds potential as a valuable tool for improving student engagement in writing and fostering critical thinking skills. The case study suggests that ChatGPT can be more than just a text generator; it can serve as an interactive resource for students to analyse and learn from model arguments (sentence skeletons), in-creasing their understanding of cohesive essay structure and logical reasoning. Overall, these insights propose a dual role for ChatGPT in educational settings – not merely as a source of content, but as a catalyst for developing essential academic skills.
Keywords: argumentative essays; argumentativni eseji; ChatGPT; critical thinking; ELT; essay writing; kritično mišljenje; pisanje esejev; poučevanje angleščine